1979
DOI: 10.1007/bf00427522
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of piracetam (UCB 6215 nootropyl) on chronic schizophrenia

Abstract: A study is described of effects of a nootropic drug on chronic schizophrenia. The nootropic drugs act on the central nervous system with the cerebral cortex as their target. Chronic schizophrenic patients on the drug showed improvement in object naming and in tests where the patient was required to indicate the number of times he had been tapped. Improvements were also noted in learning and memory tasks. In dichotic listening the patients showed a reduction in the amount of incorrect verbal responses produced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The relationship between thickness and metabolic rate has unfortunately not been studied. Several studies of callosum transfer functioning in schizophrenia have also suggested deficits more clearly consistent with reduced metabolism [34][35][36][37][38][39], Jaynes [40] presented a theory sug gesting that the disconnection of the hemispheres in the bicameral mind of early man later became more inte grated as consciousness developed. He suggested that schizophrenia may represent vestiges of bicamerality.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between thickness and metabolic rate has unfortunately not been studied. Several studies of callosum transfer functioning in schizophrenia have also suggested deficits more clearly consistent with reduced metabolism [34][35][36][37][38][39], Jaynes [40] presented a theory sug gesting that the disconnection of the hemispheres in the bicameral mind of early man later became more inte grated as consciousness developed. He suggested that schizophrenia may represent vestiges of bicamerality.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the therapeutic potential of AMPA receptor modulators has come from preclinical studies demonstrating that modulators, including biarylpropylsulfonamides, improve performance of animals on a variety of cognitive tasks that require multiple types of mnemonic processes (Staubli et al, 1994a;Hampson et al, 1998;. More importantly, several clinical studies have demonstrated that allosteric modulators can enhance cognitive function in both healthy and aged subjects, as well as in patients with Parkinson's disease and schizophrenia (Dimond et al, 1979;Oepen et al, 1985;Ingvar et al, 1997). Collectively, these data support the possibility that positive modulation of AMPA receptors may be a novel therapeutic approach for cognitive deficits in a variety of disorders, particularly those that are associated with reduced glutamatergic signaling.…”
Section: Structural Implications For Ly404187 Modulationmentioning
confidence: 99%
“…Support for the therapeutic potential of AMPA receptor potentiators comes from early clinical studies with the pyrrolidinone compounds, piracetam and aniracetam. These studies showed promising results in treating cognitive deficits associated with several neurological diseases, including Parkinson's disease, Alzheimer's disease, and schizophrenia (20,53,76). The cognitive enhancing effects of these drugs prompted their informal classification as "nootropic agents" (i.e., compounds that facilitate learning and memory).…”
Section: Introductionmentioning
confidence: 99%